Quality of Service Evaluation Modern Retail Based On Importance Performance Analysis Method - Utami, Melia Dwi; Putri, Novaryani; Satyawati, Ade Nopi; Ayu Giantari, I Gusti Ketut (TALENTA Publisher, Universitas Sumatera Utara, 2023)
The main focus of the study is to analyze important attributes in modern retail to know the performance of modern retail. The Importance-Performance Analysis (IPA) method, is an analytical method used to determine the level of performance of modern retail management in creating service quality attributes to modern retail customer perceptions. This study involved 100 respondents who were at least 18 years old and made purchases at Indomaret at least once a month or in the last three months. Research respondents were randomly selected using online survey methods. The results showed that there are four attributes of the indicators (RA1, EP1, TE4 and TE7) were the top priority at Indomaret outlets in Denpasar City. This means that Indomaret must prioritize which indicators are considered important in accordance with customer expectations. However, when viewed from the average value of the lowest level of performance, it is indicated by the indicator (TE7), namely the adequate parking area. Customers have the perception that Indomaret has not been able to provide adequate parking in accordance with consumer expectations. So that this is a concern in the future implementation of Indomaret management in Denpasar City to improve the performance of these indicators is to add sufficient parking space in accordance with current consumer needs.